The Effect of Level Testosteron e Addition in Diluents and Level Dilution on Speed Movement and Abnormality of Kedu Chicken Sperm - Susanto, Agus; Wahyuningsih, Rachmawati; Pramono, Edy (ANIMAL PRODUCTION, 2002)
The research entitled âThe Effect of Level Testosterone Addition in Diluents and Level Dilution on Speed Movement and Abnormality of Kedu Chicken Spermâ was conducted in Laboratory of Physiology and Reproduction, Faculty of Animal Science, UNSOED, started at August 15th to September 15th , 2001. The aims ofÂ  this research were to obtain influences of level testosterone and dilution on speed movement and secondary abnormality kedu chicken sperm and obtain interaction between the treatments. The tapped sperm from nine kedu chickens were used in this research. This Experiment was performed 4 x 3 Factorials with RandomizedÂ  Completely Block Design (RCBD) as the basic design. The treatment combinations were level testosterone 0, 300, 600 and 900 Î¼g (t0, t1, t2 and t3) and level of dilution 4, 6 and 8 time (in a row p1, p2 and p3). The tapping period was replicated four times as a group (replicated) with two days interval. The result of this research showed that the interaction between level of testosterone addition and level of dilution gave a non-significant effect to speed movement sperm but significant to abnormality of kedu chicken sperm. The group gave a significant influence (P<0.05) to speed movement sperm and non significant to sperm abnormality. The interaction of level testosterone addition and level dilution of kedu chicken semen (T x P) has a quadratic regression to sperm abnormality with regression comparison is Y = 24.418 â 0.014 X +1.187E â 05 XÂ², with peak point is (543.76: 20.23) of correlation coefficient (r) 0.55 and determination coefficient (RÂ²) as 30.34%. The addition of 600 Î¼g testosterone level with 6 level dilutions was the best to defend sperm abnormality. (Animal Production 4(2): 60-70 (2002)Â Key Words : Spermatozoa, Kedu Chicken, Testosterone, Dilution, Speed Movement and Abnormality